Modelos de nicho, mudanças climáticas e a vulnerabilidade do clado Perissodactyla ao longo do tempo. - Gatti, Andressa (2013)
The Earth has undergone several climate changes in the past, and the latest occurred during the glacial-interglacial cycles in the Quaternary, resulting in habitat loss, during ocean expansions and reductions, and several ecosystem changes. Numerous extinctions of that time are associated with "natural” climate change. However, the predictions indicated that climate change caused by human activities is now themajor threat to biodiversity. In response to climatic fluctuations, the distribution of some species may change, or species can move to new suitable areas. But this will depend on their ability to disperse and environmental characteristics in an anthropicecosystem. Thus, it is essential to identify the most important characteristics that make species more vulnerable to those changes. In this context, the clade Perissodactyla was a good model to test our hypotheses, because they are a group of large herbivorous mammals extremely threatened, that went through numerous environmental changes since its origin. I evaluated the influence of climate change on the Perissodactyla clade, on a wide time scale, ranging from the Quaternary (from the Last Interglacial) to the future (2080). I used two approaches: i) the relationship between the characteristics of the niche and the vulnerability of the clade in the future, and ii) the influence of climate on the distribution of environmentally suitable areas of Tapirus terrestris, in the past and future. To test the predictions, I used an Ecological Niche Modeling, which has been one of the most relevant approaches to predict changes in the species distributions. I used different sets of climate models (i.e. paleoclimate, present and future climates) and modeling procedures. The results indicated that the Perissodactyla showed distinct niche characteristics. Generalist species may also suffer negative effects of climate change. Furthermore, most of the species had idiosyncratic responses. Another important point is that barriers may have limited the dispersion of these species to new areas environmentally appropriate because several of these Perisodactyla occurred in areas highly threatened by climate change. The evaluation of the response of T. terrestris(the species most climatically generalist), to different climate scenarios, suggests that the most critical condition that prevailed during the UMG reduced the geographical extent of areas climatically suitable, with subsequent expansion. If the weather was not a very serious problem in the evolutionary history of the lowland tapir, the challenge to conserve this viiitaxon today and in the future may be much higher. Even if the total size range itself does not change as a response to climate variations, predicting the suitability of the environmental changes, along the distribution of tapirs, can help us to prioritize areas for their conservation. Thus, the disappearance of the climatic conditions and the emergence of new environmentally suitable areas should be considered in future management plans, especially concerning to creation of new protected areas for both T. terrestrisas for other Perissodactyla species